Las causales de anulación del laudo arbitral en la ley de arbitraje del Perú - Castillo Freyre, Mario (2014)
In this article, the authors discuss the implications of all grounds for annulment of an arbitration award stipulated by the Arbitration Act of Peru. They also refer to a number of cases not covered by that law, stating their views in relation to each of them.